Nocardia brasiliensis Infection Complicating Cryptogenic Organizing Pneumonia - Alison M. Fernandes; Jason C. Sluzevich; Isabel Mira-Avendano (Case Reports in Pulmonology)
Pulmonary nocardiosis is a severe and uncommon opportunistic infection caused by Nocardia species. We present a patient with cryptogenic organizing pneumonia who was receiving long-term immunosuppressive therapy, whose treatment course was complicated by cutaneous and pulmonary nocardiosis. Tissue cultures confirmed Nocardia brasiliensis. Nocardiosis should be a diagnostic consideration for patients treated with long-term immunosuppression who have worsening pulmonary symptoms and relapsing pustular skin lesions.